Future therapeutics for the induction of peripheral immune tolerance in autoimmune disease and organ transplantation. - Cobbold, S (2009)
Rodent models of transplantation and autoimmune disease have demonstrated that it is possible to induce lifelong and specific immunological tolerance to both self and graft antigens in the absence of any continued immunosuppression. If this situation could be achieved clinically, it would avoid many of the longer-term complications of immunosuppression, such as the increased risk of infection, cancer and other side effects, such as nephrotoxicity. In this review, we shall consider the interplay between regulatory T cells, dendritic cells and the tissue itself, and the resulting local protective mechanisms that are coordinated to maintain the tolerant state and an acquired local immune privilege. The current status of attempts to apply tolerogenic approaches to the clinical treatment of autoimmune diseases and to induce either tolerance to organ grafts or sufficient immune regulation so that conventional immunosuppression can be minimized will also be considered.